Forester Preferences on Revising Silvics of North America: A Survey of Registered Foresters in Four States. Issue 1 (22nd July 2021) - Merry, Krista; Bettinger, Pete; Siry, Jacek; McNulty, Steve; Gavazzi, Michael
Abstract: Silvics of North America ( SNA ) is a widely used silvicultural manual. However, the last SNA was published in 1990. Therefore, 2, 589 registered foresters were surveyed across four US states to answer two broad questions: (1) Should SNA be updated? And (2) would an updated SNA still be a useful tool for forest management? Most respondents indicated that the type and extent of content contained in the previous version of SNA was still desirable today. Aside from updating all sections with recent research findings, expansion was suggested for ecosystem services provided by species. An update to maps provided in SNA, through changes to natural ranges of tree species and other aesthetic improvement, was suggested by most survey respondents. These findings support the conclusion that the SNA would still be an essential source of information if 21st-century issues such as climate change impacts and adaptation measures were included in the update.